Growth and water status of cowpea under salt stress and exogenous melatonin application /Crescimento e status hidrico do feijao-caupi sob estresse salino e aplicacao exogena de melatonina - de Oliveira, Pablo A.H; de Lima, Francismaria F; da Silva, Jessica P.P; Silva, Ilmara B.M; da Silva, Toshik I; da Silveira, Lindomar M; Junior, Aurelio P. Barros; da Ribeiro, Joao S.E (Revista brasileira de engenharia agrícola e ambiental, 2025)
Cowpea is a species considered sensitive to salt stress, with losses in growth and yield from the irrigation water electrical conductivity of 3.3 dS [m.sup.-1]. Melatonin is a promising tool with an attenuating effect on abiotic stresses. Thus, this study aimed to evaluate the water status and growth of 'BRS Tumucumaque' cowpea as a function of irrigation water salinity and exogenous melatonin application. The experiment was conducted in a greenhouse, in a randomized block design, in a 3 * 3 factorial scheme, with three replicates and two plants in each experimental unit. The first factor consisted of three salinity levels in the irrigation water (0.5, 3.0, and 5.0 dS [m.sup.-1]), and the second factor of three melatonin concentrations (0, 0.5, and 1 mM). At 41 days after sowing, plant height, stem diameter, number of leaves and leaflets, root length, leaf area, dry mass of leaves, petiole, stem and root, relative water content, electrolyte leakage, leaf mass per unit area and succulence were analyzed. Increasing salinity concentrations reduced most growth variables and increased electrolyte leakage. Exogenous application of melatonin did not have a significant effect on the attenuation of salt stress in cowpea. Key words: Vigna unguiculata (L.) Walp., salinity, biostimulant, water relations, biomass production O feijao-caupi e uma especie considerada sensivel ao estresse salino, com perdas no crescimento e produtividade a partir da condutividade eletrica da agua de irrigacao de 3,3 dS [m.sup.-1]. O uso de melatonina tem se mostrado uma ferramenta promissora com efeito atenuador de estresses abioticos. Assim, o objetivo do estudo foi avaliar o crescimento e o status hidrico do feijao-caupi 'BRS Tumucumaque' em funcao da salinidade da agua de irrigacao e aplicacao exogena de melatonina. O experimento foi conduzido em casa de vegetacao, em delineamento em blocos casualizados, em esquema fatorial 3 * 3, com tres repeticoes e duas plantas em cada unidade experimental. O primeiro fator foi constituido por tres niveis de salinidade na agua de irrigacao (0,5; 3,0 e 5,0 dS [m.sup.-1]); e o segundo fator, por tres concentracoes de melatonina (0, 0,5 e 1 mM). Aos 41 dias apos a semeadura, foram analisadas a altura da planta, diametro do caule, numero de folhas e de foliolos, comprimento radicular, area foliar e massa seca das folhas, peciolo, caule e raiz, conteudo relativo de agua, extravasamento de eletrolitos, massa foliar por unidade de area e suculencia. O aumento das concentracoes de salinidade reduziu a maioria das variaveis de crescimento e aumentou o extravasamento de eletrolitos. A aplicacao exogena de melatonina nao teve efeito significativo na atenuacao do estresse salino no feijao-caupi. Palavras-chave: Vigna unguiculata (L.) Walp., salinidade, bioestimulante, relacoes hidricas, producao de biomassa